Reka Cipta Alat Filtrasi Alami Menggunakan Bahan Recycle Sebagai Alat Penyaring Air Limbah Rumah Tangga - Handi Wilujeng Nugroho; Kurniawan Hamidi (Journal of Green Engineering for Sustainability, 2023)
Rapid industrial growth worldwide, especially in Indonesia, has posed threats to the environment and public health. Environmental pollution is mainly caused by domestic wastewater generated from households, businesses, and residential areas. Types of domestic wastewater that need attention include human feces or waste, urine, detergents, soaps, and food scraps. Wastewater pollution from households has become increasingly critical due to the rise in household activities and urbanization in Indonesia. To address the issue of household wastewater pollution, efficient wastewater management systems and increased public awareness are necessary. The implementation of filtration technology is a crucial solution to maintain water quality. Filtration is a process of separating solid particles from liquids using filtering media or screens. The results of filtration can produce cleaner and safer water, and this technology continues to be developed to meet the demand for high-quality and safe water. This experiment aims to create a simple filtration bottle using recycled materials and demonstrate its effectiveness in reducing the content of household wastewater. The filtration process resulted in a 79.32% reduction in COD content, an 85% reduction in TSS content, and a 91.3% reduction in turbidity. By utilizing recycled materials and efficient filtration technology, it can help mitigate the negative impact of domestic wastewater on the environment. In conclusion, the utilization of recycled materials as a simple filtering tool can reduce the content of household wastewater and contribute to maintaining a clean and healthy environment. The awareness and participation of the community in using this filtering tool can have a greater positive impact on the environment.